The Effect of the Humanistic Model on Arabic Learning Outcomes of Students at MTs Al-Falah Nipa Ambalawi - Sri Jomila Oktari; Muhammad Fadhil Hadziq; Fika Nurhumaidah; Bulqis (Al-Muhawaroh: Jurnal Pendidikan Bahasa Arab, 2026)
This study aims to examine the effect of the humanistic learning model on students’ Arabic language learning outcomes at MTs Al-Falah Nipa Ambalawi. Addressing gaps in previous research that largely emphasized theoretical discussion and affective aspects without rigorous quantitative measurement, this study employed a quantitative approach using a quasi-experimental pretest–posttest control group design. The population consisted of 56 seventh-grade students divided into experimental and control groups. Data were collected through a validated and reliable Arabic learning outcomes test and analyzed using SPSS version 23. Prerequisite tests of normality and homogeneity confirmed compliance with parametric assumptions. Hypothesis testing using the paired sample t-test revealed a calculated t-value of 3.418 with a significance value of 0.002 (<0.05), indicating a statistically significant effect of the humanistic learning model. These findings formally answer the research objective by demonstrating that the humanistic model significantly improves students’ Arabic achievement. The study provides empirical evidence that student-centered and supportive instruction enhances measurable cognitive outcomes, contributing both theoretically and practically to the development of humanistic approaches in Arabic language education.